The Impact of the Hand Calculator Prism Model on Fourth-Grade Students' Computational Abilities - Jumaroh, Juju; Faiz, Aiman; Afendi, Arief Hidayat (Papanda Publisher, 2025)
Indonesian students consistently demonstrate low mathematical literacy in international assessments, with computational difficulties stemming from negative perceptions and monotonous instructional approaches. This study examined the effectiveness of the Hand Calculator Prism model—a finger-based manipulative method—in enhancing fourth-grade students' computational abilities. Employing a pre-experimental one-group pretest-posttest design, 30 fourth-grade students from SDN 1 Jamblang participated in five structured learning sessions. Data collection utilized computational ability tests, observation sheets, and Likert-scale questionnaires. Analysis involved descriptive statistics, paired sample t-tests, Cohen's d effect size, and Normalized Gain calculations. Significant improvement was observed from pretest (M = 51.27, SD = 8.91) to posttest (M = 85.53, SD = 14.24), yielding a mean gain of 34.26 points. The paired t-test confirmed statistical significance (t = -15.741, p < 0.001) with an exceptionally large effect size (d = 2.86). The N-Gain value of 0.6110 indicated medium-to-high effectiveness. Student responses demonstrated excellent engagement (87% Response, 82% Acceptance). Observational data revealed progressive improvement across implementation sessions, particularly in conceptual understanding and problem-solving activities. The Hand Calculator Prism model represents a viable, resource-accessible pedagogical approach that significantly enhances elementary students' arithmetic skills while fostering positive attitudes toward mathematics learning.